Urban Memory and Identity: Exploring the Social Significance of Preservation of Historic Buildings - Ma Wenqin (SHS Web of Conferences)
This paper aims to explore the social significance of the preservation of historical buildings in the preservation of urban memory and the construction of social identity. With the rapid progress of urbanization, historic buildings are facing unprecedented challenges, and these ancient buildings are not only the material heritage of the city, but also carry rich collective memory and cultural value, and are an important part of local identity. By analyzing the value of historic buildings, the principles of conservation, and their role in passing on the memory of cities, the paper emphasizes the importance of historic buildings as witnesses to the history of cities, and points out that conservation efforts help to strengthen community identity and promote the preservation of local identity in the context of globalization. In addition, this paper also examines how historical buildings reflect the continuity of urban development in the time dimension, providing valuable references for future urban development. In the process of globalization and modernization, attention should be paid to the role of historical buildings in maintaining the uniqueness and diversity of cities, and they should be included in urban development planning. Finally, the paper calls for the exploration of innovative conservation models and encourages interdisciplinary cooperation to deepen research in this field to ensure that historic buildings can continue to be properly protected and developed as part of the common cultural heritage of mankind. Through the above discussion, this paper reveals the key role of the preservation of historic buildings in maintaining and enriching the cultural identity of cities.